Designing salt-induced polymer-polymer biphasic systems for optimized extraction of Monascus ruber biopigments obtained by fermentation of xylose-based medium - Lino, Nayara K.B.; Arruda, Gabriel L.; Lourenço, Felipe R.; Santos-Ebinuma, Valéria C. [UNESP]; da Silva, Silvio S.; Santos, Júlio C.; Lopes, André M. (Elsevier, 2025)
The widespread use of synthetic colorants raises biosafety and environmental concerns, highlighting the need for natural alternatives like Monascus biopigments. These pigments possess antimicrobial and antioxidant properties, offering biotechnological and biopharmaceutical potential. Cost-effective biopigment production using xylose-rich hydrolysates from lignocellulosic biomass has been explored, but its sustainable downstream processing is crucial. Traditional liquid-liquid extraction with volatile organic compounds (VOCs) is harmful, prompting the use of eco-friendly aqueous biphasic systems (ABS) based on green chemistry principles. This study investigated the stability, partitioning, and purification of Monascus ruber biopigments (yellow, orange, and red) from fermented broth using ABS composed of polyethylene glycol (PEG), sodium polyacrylate (NaPA), and salts (MgSO4 and CaCl2). Binodal curves showed MgSO4 enhanced phase separation more effectively than CaCl2. Biopigments demonstrated high stability over 65 days and preferentially partitioned into the PEG-rich phase (K Biopigments = 3–14), with recovery (REC Top) values of 52–79 %. Optimal ABS conditions (18 % wt/wt PEG8000, 10 % wt/wt NaPA1200, and 0.3 M MgSO4) yielded biopigment REC Top of 71–80 %, K Biopigments of 12–15, and high selectivity over proteins (S = 14–19). Protein contaminants predominantly partitioned into the NaPA-rich phase, achieving a 10-fold purification. These findings support the stabilization and eco-friendly extraction of biopigments for bio-industrial applications.